Effects of Virtual Reality-Based Distraction of Pain, Fear, and Anxiety During Needle-Related Procedures in Children and Adolescents - Wang, Yan; Guo, Liangmei; Xiong, Xinjuan (Frontiers in Psychology, 2022)
Background: Needle-related pain, fear, and anxiety can be a deterrent to treatments in children and adolescents. Virtual reality (VR) can be used to manage the poor experience of needle procedures. Objective: This meta-analysis aimed to examine the effects of VR on pain, fear, and anxiety related to needle procedures in children and adolescents. Methods: PubMed, EMBASE, and the Cochrane Library were searched for potentially eligible studies published up to June 2021. The outcomes were pain assessed by the Wong-Baker Faces Pain Scale (WBS) or Faces Pain Scale-Revised (FPS-R), fear assessed by Children’s Fear Scale (CFS), and anxiety assessed by Children’s Anxiety Meter (CAM) or CFS. Because of expected heterogeneity among studies, all analyses were conducted using the random-effects model. Results: Ten studies were included (571 children in the VR group and 575 in the control group). Based on the WBS, VR reduced pain, either self-reported (WMD=-2.17, 95%CI: -3.37,-0.97), parent-reported (WMD=-3.52, 95%CI: -4.62,-2.42), nurse-reported (WMD=-3.29, 95%CI: -5.59,-0.99), and physician/investigator-reported (WMD=-3.48, 95%CI: -5.93,-1.04). Using the FPS-R, VR reduced needle-related pain compared with controls (WMD=-0.85, 95%CI: -1.64,-0.06). Similar results were observed for fear (children/adolescents: WMD=-1.52, 95%CI: -2.18,-0.86; parents: WMD=-1.71, 95%CI: -2.30,-1.13; nurses: WMD=-1.55, 95%CI: -2.47,-0.63; physicians/investigators: WMD=-0.59, 95%CI: -1.00,-0.18) and anxiety (self-reported: WMD=-2.79, 95%CI: -4.07,-1.54; parent-reported: WMD=-3.87, 95%CI: -5.58,-2.15; nurse-reported: WMD=-4.64, 95%CI: -6.56,-2.71; physician/investigator-reported: WMD=-2.06, 95%CI: -4.13,-0.00). Conclusion: A VR-based intervention could reduce needle-related pain, fear, and anxiety in children and adolescents.